MITOS YUUREI DALAM KOMIK KYOUKAI NO RINNE KARYA RUMIKO TAKAHASHI - Salvinia Sugama, I Gusti Ayu (Humanis, 2015)
This research entitles “ Yuurei myth in Kyoukai No Rinne Manga by Rumiko Takahasi”. The reason for this title was choosen is because Kyoukai No Rinne manga consist of many aspect that related to Yuurei myth. The purpose of this research is to know the depiction of yuurei myth that can be found in Kyoukai No Rinne Manga and the characteristic of yuurei. The Method choosen for this research is Descriptive Analysis and Informal Method. The theory used is Antropology Literature Theory and Semiotics Theory by Marcel Danesi. There are various kind of yuurei that can be found as the result of this research , each with different depiction. First, yuurei that stay in one place: Jibakurei, Puuru no Utahime, Joshirei, Yuureihama, Obake Sugi. Second, Yuurei who stay inside things: Denwarei, Nuigurumi, Fumibako, Noroi no Chouridai. Third, Living yuurei: Kao no Nai Onna, Te, Tosaken, Katei Kyoushi no Ikiryou. And last, The sad Yuurei:Ochimusha, Bero, Wani Onna. The characteristic of each yuurei is different. From sixteen yuurei, positive elements can be found such as happiness, affection, fidelity, forgiveness, thoughtfulness and regret. Whereas, the negative elements consist of greed, pride, shyness, carelessness, selfishness, spitefulness, hypocritical, and naughtiness.